Implementation of Plastic Shredding Machine for Waste Processing in Wukirsari Village - Purnawan; Dwi Bekti, Rokhana; Suparni Setyowati Rahayu; Purwanto, Yuli; Ratno, Jovin; Andang Novianta, Muhammad (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The village of Wukirsari faces the problem of plastic waste, which is increasingly generated by community activities such as households, tourism, agriculture, and fishing. The Organization of ‘Sadar Lingkungan Balangan’ Group is one of the waste management groups in Wukirsari that has limitations in waste processing tools. Therefore, an effort was made to manage waste based on appropriate technology by using a plastic shredder. The goal of this program is to provide a plastic shredding machine to help reduce waste piles and increase the selling value of waste. The program has been running with stages of socialization and FGD, implementation of TTG, training and monitoring and evaluation. With a capacity of 90 - 100 kg/hour, the use of this machine can avoid the accumulation of waste. Waste can be recycled, waste accumulation is reduced and waste has more value. In addition, the group has received training and the support of Wukirsari Village will ensure that the sustainability of the program will continue.